The role of the PB2 627-domain in influenza A virus polymerase function - Nilsson, B; te Velthuis, A; Fodor, E (American Society for Microbiology, 2017)
The RNA genome of influenza A viruses is transcribed and replicated by the viral RNA-dependent RNA polymerase composed of the subunits PA, PB1 and PB2. High-resolution structural data revealed that the polymerase assembles into a central polymerase core and several auxiliary highly flexible, protruding domains. The auxiliary PB2 cap-binding andthe PA endonuclease domains are both involved in cap-snatching, but the role of the auxiliary PB2 627-domain, implicated in host range restriction of influenza A viruses, is still poorly understood. Here we use structure-guided truncations of the PB2 subunit to show that a PB2 subunit lacking the 627-domain accumulates in the cell nucleus and assembles into a heterotrimeric polymerasewith PB1 and PA. Furthermore, we show that a recombinant viral polymerase lacking the PB2 627-domain is able to carry out cap-snatching, cap-dependent transcription initiation as well as cap-independent ApG dinucleotide extension in vitro, indicating that the PB2 627-domain of the influenza virus RNApolymerase is not involved in core catalytic functions of the polymerase. However, in a cellular context, the 627-domain is essential for both transcription and replication. In particular, we show that the PB2 627-domain is essential for the accumulation of the cRNA replicative intermediate in infected cells. Together, these results further our understanding of the role of the PB2 627-domain in transcription and replication of the influenza virus RNA genome.